History of the Periodontics Department of "Raúl González Sánchez" Dental School. Havana, Cuba - Gladys Rodríguez Méndez (Universidad de Ciencias Médicas de La Habana, 2019)
The history of the creation of the Periodontics Department of "Raúl González Sánchez" Dental School of Havana, Cuba is analyzed.  The approval of the Specialty in Periodontics in 1967 contributed to its designation.  Here it is described that, from the very beginning, the contents of Periodontics were taught independently in two subjects until they were consolidated in only one subject with a recommended bibliography.  The role of the department in the implementation of different syllabuses and curricula taught in both undergraduate and postgraduate courses is also explained as well as its contribution to the training of Cuban and foreign dentists, periodontists, and dental students.   Keywords: Curriculum, undergraduate, postgraduate, periodontics.